Making connections and promoting the profession: Social media use by World Federation of Occupational Therapists member organisations - Anita L Hamilton; Susan C Burwash; Merrolee Penman; Karen Jacobs; Angela Hook; Sarah Bodell; Ritchard Ledgerd; Marilyn Pattison (Digital Health, 2016)
Background World Federation of Occupational Therapists (WFOT) member organisations comprise 77 national occupational therapy organisations across the world. Each national organisation interacts with its members and the public using diverse methods. Increasingly, national organisations are broadening their communication methods. Objective The objective of this study was to examine if and how occupational therapy organisations are using social media for communication, and if so, the types of concerns or barriers they experience and what role they anticipate social media might play in the near future. Methods An online survey was developed; 57 of 77 WFOT member organisations responded. Findings This study identified that WFOT national organisations are using social media, to varying degrees, with or without an individual formally assigned to manage social media. Respondents reported that they used social media to: communicate with members, promote the organisation and promote the profession. Commonly expressed needs included assistance with guidelines for ethical social media use, developing technical expertise, and recognition of limits of time and competing priorities. Recommendations arising from this research are at the global, national, local and individual levels and incorporate active dissemination and pure diffusion approaches. Taking steps to increase the use of social media could indirectly impact occupational therapy practice through enhancing organisations’ abilities to support practitioners to enhance their practice. Limitations and recommendations for further research Although 57% of WFOT member organisations returned usable responses, there may be some additional perspectives that were not captured. It would be helpful to contact non-responding organisations to explore their social media use and plans. Further research could examine how future initiatives put in place by WFOT impact social media use by member organisations.